2019
DOI: 10.2109/jcersj2.19016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phase and thermoelectric properties of thin film SrSi<sub>2</sub>

Abstract: We firstly prepared SrSi 2 thin films on insulating substrates and measured their thermoelectric properties. Thin films of SrSi system were deposited on (0001) Al 2 O 3 substrates by radio frequency magnetron sputtering method at various deposition temperatures and under various total deposition pressure. Constituent phases primary depend on the deposition temperature. The films deposited below 600°C consisted of amorphous or the metastable CaSi 2 structure phase. CaSi 2 structure phase was obtained at 600°C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…A comparison of the power factor of the obtained ptype Ca-Mg-Si film with those of the other p-type silicides reveals that the power factor of the present Ca-Mg-Si film is smaller than those reported for Sr-Si and Si-Ge films. [25][26][27] On the other hand, the present n-type films show better properties compared with the other silicides, but is smaller than widely investigated materials such as Bi-Te and Ag-Se. 28,29 However, it is possible to improve the present power factor by using doping to optimize the carrier concentration.…”
Section: Electrical Propertiesmentioning
confidence: 74%
“…A comparison of the power factor of the obtained ptype Ca-Mg-Si film with those of the other p-type silicides reveals that the power factor of the present Ca-Mg-Si film is smaller than those reported for Sr-Si and Si-Ge films. [25][26][27] On the other hand, the present n-type films show better properties compared with the other silicides, but is smaller than widely investigated materials such as Bi-Te and Ag-Se. 28,29 However, it is possible to improve the present power factor by using doping to optimize the carrier concentration.…”
Section: Electrical Propertiesmentioning
confidence: 74%
“…15,16 It has been confirmed that SrSi 2 prepared by a sputtering method has two polymorphs. 13 The most stable semimetal cubic phase (hereafter described as the cubic phase) was obtained at above 700 °C, which is good for TE materials around room temperature. The other metastable phase with a layered structure (hereafter described as the layered phase), which formed below 600 °C, shows lower electrical resistivity and higher carrier density than the cubic phase, namely, benign metals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10−12 Moreover, even when SrSi 2 was made into thin films, the power factor was ascertained to be less degraded in previous reports than was the case with other materials, in contrast to other materials. 13 Therefore, SrSi 2 seems to be advantageous for miniaturizing materials for use as heat sources for integrated devices, such as central processing units.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] However, most of these high-performance films still have the problems of relatively high cost, narrow applicable temperature, etc. While inexpensive thin films like oxides, [8][9][10] silicides, [11,12] borides, [13] Heusler alloys, [14,15] skutterudites, [16,17] etc., in general, have tended to show lower conversion efficiencies. Enhancement of conversion efficiency is limited mainly by two factors.…”
Section: Introductionmentioning
confidence: 99%